NOVEL DIBALIK SENJA BY MOH. RIFA'I (A STUDY OF LITERATURE ECOLOGY) - Sally Andriani Wukalen (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to described environmental damage damage the environment, protection of the universe and the impact of environmental recovery in novel Di Balik Senja by Moh Rifai. Research qualitative study used descriptive qualitative type methods. Primary data the come of novels Di Balik Senja Karya Moh Rifai. Analysis technique using qualitative analysis descriptive reviews ecology literary environmental destruction, covering damage the environment, maintenance and the impact environment environment maintenance. Based on the research other it can be concluded some respects between the environmental damage in in a novel Di Balik Senja Karya Moh Rifai, the on landslides, maintenance with mountain environment namely set sojol be forest heritage, nature and the impact the habitats of flora and fauna maintenance back to good.